2005
DOI: 10.1248/cpb.53.90
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Quaternary Ammonium Ions and Dipeptides: Positive Anion Allosteric Effect

Abstract: Noncovalent interactions are of fundamental importance in determining the highly dimensional structures and fundamental properties of molecular systems in biology, chemistry, and materials sciences. Relatively strong non-covalent bonding such as salt bridge and hydrogen bonding has been extensively investigated. In contrast, weak noncovalent bonding such as p-p, CH-p and cation-p interaction is now known to play important roles in the stabilization of the complexes 1-3) but is not well understood, because the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…Herein, we present a systematic study in order to establish how modifications of the tertiary amine component and counterion could influence the stability, versatility and coupling efficiency of this family of coupling reagents. This proposition was additionally supported by the previously reported influence of the counterion on the stability of coupling reagents19a as well as disruption of the peptide chain conformation in the presence of the ions 19b…”
Section: Introductionsupporting
confidence: 63%
“…Herein, we present a systematic study in order to establish how modifications of the tertiary amine component and counterion could influence the stability, versatility and coupling efficiency of this family of coupling reagents. This proposition was additionally supported by the previously reported influence of the counterion on the stability of coupling reagents19a as well as disruption of the peptide chain conformation in the presence of the ions 19b…”
Section: Introductionsupporting
confidence: 63%
“…(2-Hydroxyethyl)-triethylammonium iodide [(2OHE)-triEA] (Kasuga et al, 1969) was made from 2-diethylaminoethanol and ethyl iodide, and is a white solid. Benzyltrimethylammonium iodide (BtriMA) (Ito et al, 2005) was made from dimethylbenzylamine and methyl iodide, and is a white solid. Benzylethyldimethylammonium iodide (BEdiMA) (Short and Biermacher, 1962) was made from dimethylbenzylamine and ethyl iodide, and is a white hygroscopic solid.…”
Section: Methodsmentioning
confidence: 99%
“…Previous work using dipeptides as synthetic hosts has shown that they can bind ammonium cations in chloroform. 38 Moderate affinity between a tyrosinebased dipeptide host and acetylcholine were measured in chloroform (K d = 7.69 mM). We created new hosts based on this synthetic scaffold with two key features: the addition of carboxylates for improved electrostatic attraction and water solubility and the introduction of indole-N-benzyl substituents as additional aromatic surfaces for cation binding ( Figure 4).…”
Section: Tetrazolates and Indole Carboxylatesmentioning
confidence: 99%